P11.38.A Case reports on aggressive Pilocytic astrocytoma in TYA and adults: patient tailored approach or standard of care?. (5th September 2022) - Gupta, S; Brazil, L; Swampillai, A; Al-Salihi, O
Abstract: Background: Pilocytic astrocytoma (piloA) is a low grade brain tumour and most of the literature is based on paediatric patients with limited data on adults. Surgical resection followed by adjuvant treatment for recurrent lesions is standard of care. While previous literature was mainly based on historical classification, molecular analysis of tumour is adding to the subgroup classification. Material and Methods: We are reporting 3 cases of adult piloA treated at our institute. Results: Case1: 31y female with headaches and visual problems was diagnosed with optic nerve glioma, biopsy confirmed piloA, and was treated with conventional radiotherapy 50Gy/30fr. A month later developed CSF dissemination requiring 10xTemozolamide. Two years later, developed L5 and S2 deposits which were resected and confirmed piloA. 5 years later there was progression of primary disease treated with 12xTemozolamide and a year later developed further progression and hydrocephalus. She received 1xPCV and succumbed to disease at the age of 42. Case 2 : 29y female with severe dizziness on moving head, worsening headaches, word finding difficulty, and positive family history of anaplastic astrocytoma, was diagnosed with Tectal plate lesion. Surgical debulking was performed and pathology showed piloA with Methylated MGMT promoter, IDH wild-type, H3K27M negative, and no BRAF fusion. 3 years later developed recurrence which was treated with chemotherapy (5xPCV: 6 th omitted due to recurrent infections) as patient was reluctant for radiotherapy. Follow up scans 6 months post chemotherapy remain stable. Case 3 : 24y female with background of 2 haemorrhagic strokes, left spastic hemi-paralysis and left hemianopia, and negative family history, had a biopsy performed for Right Mesotemopral Cavenous Angioma. Pathology showed low grade neoplasm favouring Ganglioglioma with CD34 and IDH1 negative, ATRX retained, KI-67 focal index 5%, and no BRAF fusion or mutation. Surveillance imaging showed progressively increasing suprasellar mass and right temporal region enhancement which was surgically debulked at the age of 27. Repeat pathology examination favoured piloA considering the radiological progression. Methylation array failed but immunohistochemistry showed tumour cells positive with synaptophysin, ATRX and trimethylated H3K27 retained, H3K27M, NeuN, H3G34R and CD34 negative, p53 negative, and Ki-67 3-4%. Repeat imaging 10 months later showed further progressive suprasellar tumour and enhancing lesion in the right temporal area accompanied by rapid loss of right side vision. We have planned for radical radiotherapy 54Gy/30fr with IMRT. Conclusion: There is a gap in management of piloA in adults with treatment extrapolated from paediatrics and does require further research. We want to approach other centres to establish consensus on treating such cases.